ENT 530 Business Plan : Fluffy Foaam / 'Adilah Safiah Asran ... [et al.] - Asran, 'Adilah Safiah; Mohd Salleh, Muhammad Fareez; Samsul Anwar, Nur Anis; Na'im, Nur Zahirah; Azmi, Nurul Afiqah (2019)
Fluffy Foaam is a company that provides health and hygiene products called tablet soap. Manufactured tablet soaps have three different functions for hand washing, clothes washing and for the body as well. Each function has a different scent.